Yield stress "in a flash": investigation of nonlinearity and yielding in soft materials with an optofluidic microrheometer. Issue 11 (18th February 2021) - Vitali, Valerio; Nava, Giovanni; Corno, Andrea; Pezzotti, Melissa; Bragheri, Francesca; Paiè, Petra; Osellame, Roberto; Ortenzi, Marco Aldo; Cristiani, Ilaria; Minzioni, Paolo; Bellini, Tommaso; Zanchetta, Giuliano
Abstract : An optical active microrheology technique, capable of high forces, is proposed for yield stress measurements. Abstract : Yield stress materials deform as elastic solids or flow as viscous liquids, depending on the applied stress, which also allows them to trap particles below a certain size or density threshold. To investigate the conditions for such a transition at the microscale, we use an optofluidic microrheometer, based on the scattering of an infrared beam onto a microbead, which reaches forces in the nN scale. We perform creep experiments on a model soft material composed of swollen microgels, determining the limits of linear response and yield stress values, and observe quantitative agreement with bulk measurements. However, the motion of the microbead, both below and above yielding, reflects distinctive microscale features of the surrounding material, whose plastic rearrangements were investigated by us using small, passive tracers.